(untitled) (Journal of Medicine, 2019)
Background: Diabetes mellitus is responsible for significant morbidity and mortality around the world though there is huge development regarding its treatment. Many studies showed that functional health literacy has a great impact on diabetes outcome. The study assessed the relationship between functional health literacy and glycemic control in a sample of urban diabetic patients. Materials and methods: A cross-sectional study was conducted in Bangladesh University of Health and Science Hospital, Jurain, Dhaka from January to December 2014 that included adult diabetic patients on the basis of defined selection criteria following the purposive sampling method. Functional health literacy was assessed with the short form Test of the Functional Health Literacy in Adults (s-TOFLA). Recent HbA1c was used as a measure of glycemic control and categorized into tight, fair and inadequate glycemic control. Regression models were controlled for demographic data, diabetes duration, treatment regimen, diabetes knowledge and assistance for taking medications. Results: Following the s-TOFLA scale, 60.5% of the diabetic patients had inadequate functional health literacy of them, 89.3% had inadequate glycemic control (HbA1c>8%). And those who had adequate functional health literacy (24%) of them 68.8% had tight glycemic control (HbA1c≤7%). Overall 63.0% of the respondents had inadequate glycemic control. In linear regression model low s-TOFLA scores, longer diabetes duration and lack of assistance for taking medications were associated with higher levels of HbA1c. In fully adjusted model s-TOFLA score was the variable which was more strongly associated with HbA1c (β = -0.60, P<0.001). Conclusions: The study found that low health literacy is consistently associated with inadequate glycemic control. J MEDICINE JUL 2019; 20 (1) : 19-24